Alteration in sperm characteristics, endocrine balance and redox status in rats rendered diabetic by streptozotocin treatment: attenuating role of Loranthus micranthus. (1st January 2018) - Ebokaiwe, Azubuike P.; Ijomone, Omamuyovwi M.; Osawe, Sharon O.; Chukwu, Chukwuma J.; Ejike, Chukwunonso E.C.C.; Zhang, Guolin; Wang, Fei
ABSTRACT: Objectives: Loranthus micranthus is widely used in Nigerian folklore treatment of male infertility and diabetes complications. We investigated this claim in rats rendered diabetic by streptozotocin (STZ). Methods: Induction of diabetes mellitus in adult male Wistar rats was by intraperitoneal injection of STZ (60 mg/kg). The diabetic rats were thereafter treated orally once/day with 5 mg/kg Gilbenclamide or L. micranthus (100 mg/kg or 200 mg/kg) and monitored for 14 days. Clinical observations, hormonal profile, oxidative stress parameters, glucose metabolism enzymes, histopathological examination, apoptotic marker immunoreactivity and western blotting in testes and sperm parameters were evaluated to examine effects of L. micranthus on STZ-diabetic rats. Results: L. micranthus treatment significantly reduced the blood glucose level (45.9% and 84.7% on the 7th and 14th post-treatment days, respectively); increased antioxidant status, improved microarchitecture of testes, reduced lipid peroxidation and increased BCl-2 protein expression in diabetic rats relative to control. Furthermore, treatment with L. micranthus increased steroidogenic enzymes activities, levels of steroid hormones and improved sperm quality, relative to control. Conclusion: The anti-diabetic and aphrodisiac properties exhibited by L. micranthus could be contingent on its ability to restore a balance to the compromised redox status that characterizes male reproductive dysfunction in diabetes.